2006
DOI: 10.1194/jlr.m600135-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis is enhanced by testosterone deficiency and attenuated by CETP expression in transgenic mice

Abstract: In this work, we investigated the impact of testosterone deficiency and cholesteryl ester transfer protein (CETP) expression on lipoprotein metabolism and dietinduced atherosclerosis. CETP transgenic mice and nontransgenic (nTg) littermates were studied 4 weeks after bilateral orchidectomy or sham operation. Castrated mice had an increase in the LDL fraction (136% for CETP and 179% for nTg mice), whereas the HDL fraction was reduced (230% for CETP and 211% for nTg mice). Castrated mice presented 1.7-fold highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 69 publications
2
34
0
6
Order By: Relevance
“…22,23 In addition, CETP expression stimulates the selective uptake of HDL-derived cholesteryl ester by the liver and other tissues 24 and by human adipocytes 25,26 and protects against atherosclerosis in specific conditions such as hypertriglyceridemia 27 and sexhormone deficiency. 28,29 By reducing HDL cholesterol levels, CETP has been considered a major target for developing inhibitors aimed at reducing atherosclerosis risk (for review see Clark 30 ). However, unexpected negative outcomes from large-scale clinical trial testing the CETP-inhibitor torcetrapib have seriously questioned this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 In addition, CETP expression stimulates the selective uptake of HDL-derived cholesteryl ester by the liver and other tissues 24 and by human adipocytes 25,26 and protects against atherosclerosis in specific conditions such as hypertriglyceridemia 27 and sexhormone deficiency. 28,29 By reducing HDL cholesterol levels, CETP has been considered a major target for developing inhibitors aimed at reducing atherosclerosis risk (for review see Clark 30 ). However, unexpected negative outcomes from large-scale clinical trial testing the CETP-inhibitor torcetrapib have seriously questioned this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting qualitative difference in plasma lipoproteins is that castrated Ldlr Ϫ / Ϫ mice had increased levels of esterifi ed cholesterol in plasma, a fi nding that may be due to enhanced Lcat activity under conditions of hypogonadism in these mice. Work by Casquero and coworkers ( 52 ) indicated that overexpression of human cholesteryl ester transfer protein (hCetp) in mice results in a signifi cant attenuation of the increase in atherosclerosis, following surgical castration. However, these authors reported no signifi cant difference in the body weight gain of the castrated hCetp-expressing mice compared with the non-hCetp-expressing castrated littermates.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, expression of the CETP gene has been reported to have an antiatherogenic effect in db/db obese diabetic mice, 20 in lCAT transgenic mice, 21 in ovariectomized mice, 22 in testosterone-deficient mice, 23 and in apoC-III transgenic mice with hypertriglyceridemia. 24 In the last study, however, it was also reported that expression of the Cetp gene was proatherogenic in Figure 1.…”
Section: Studies In Rodentsmentioning
confidence: 99%
“…Mice fed an atherogenic diet 14 ApoE knockout mice 15 LDL receptor knockout mice 15 ApoC-III transgenic mice with normal plasma triglyceride levels 24 ApoE3-Leiden mice 16 Aypertensive rats 17 Expression of CETP in rodents had no effect on atherosclerosis SR-B1 knockout mice 18 Expression of CETP in rodents decreased atherosclerosis db/db obese, diabetic mice 20 LCAT transgenic mice 21 Ovariectomized mice 22 Testosterone-deficient mice 23 ApoC-III transgenic mice with hypertriglyceridemia 24 B. Rabbits (rabbits have a high natural level of CETP activity) Inhibition of CETP in rabbits decreased susceptibility to diet-induced atherosclerosis in:…”
Section: Expression Of Cetp In Rodents Increased Atherosclerosis Inmentioning
confidence: 99%